Tomografia experimental de estados quânticos: impIementação de tomografia mínima. - Wanderson Maia Pimenta (2010)
This work has as a main goal the implementation of the experimental minimal quantum tomography in spatial variables using a spatial light modulator. To produce the two photons states entangled in spatial variables we use the properties of the photons produced by Spontaneous Parametric Down Conversion (SPDC) and double slits. A theoricaldescription was necessary for the understanding of the minimal tomography method. Four states which describe a tetrahedron in the Bloch sphere were chosen and associated to these states, were built four operators, making it a POVM set for tomography. For the experimental implementation of these operators, it took two calibrations of the spatial light modulator. Values of grayscales and polarization angles of input and output polarizers were determined in order to apply dierent phases and/or specific amplitude diferences between the beams that pass through each slit path. Thus, through the studyof minimal tomography and the knowledge of the operation of the modulator and their calibration, it was possible to experimentally perform the minimal quantum tomography for one and two qubits in spatial variables.